Immunological aspects of cystic echinococcosis in Erbil - Al-Sakee, Hadi M. A. (Zanco Journal of Medical Sciences (ZJMS), 2011)
Background and objectives: Echinococcus granulosus exists as a complex of different strains that differ in a wide variety of criteria that impact on the epidemiology, immunology, pathology and control of hydatid disease. This study was undertaken to investigate both humoral and cellular immune responses that are developed against hydatid cysts in Erbil. Methods: Thirty patients (9 males and 21 female) with surgically confirmed cystic echinococcosis and 10 apparently healthy individuals were included in this study. IgG ELISA was performed to asses humoral immune responses. CD4/ CD8 ratio, eosinophil count and lymphocyte transformation response were done to asses the cellular immune responses. The level of IFN-γ and TNF-α was also assayed. Results: The sensitivity of ELISA to detect anti-hydatid antibodies was shown to be 83.33%. CD4 / CD8 ratio was significantly (P< 0.001) decreased in patients with cystic echinococcosis as compared to normal control group, while eosinophil count (P< 0.001), lymphocyte transformation response (P< 0.001) and IFN-γ level (P< 0.01) were significantly increased. In contrast the level of TNFα was non- significantly changed in echinococcosis patients. Conclusion: The current study showed that the local strain of Echinococcus granulosus induces both cellular and humoral immune responses, and the number of peripheral blood CD8 T cells was significantly increased in cystic echinococcosis patients. However, hyporesponsivness to hydatid specific antigens has not been induced.